CD4 CTL, a Cytotoxic Subset of CD4+ T Cells, Their Differentiation and Function - Takeuchi, Arata; Saito, Takashi (Frontiers in Immunology, 2017)
CD4+ T cells with cytotoxic activity (CD4 CTL) have been observed in various immune responses. These cells are characterized by their ability to secrete granzyme B and perforin and to kill the target cells in an MHC class II-restricted fashion. Although CD4 CTLs were once thought to be an in vitro artifact associated with long-term culturing, they have since been identified in vivo and shown to play important roles in antiviral and antitumor immunity, as well as in inflammation. Functional characterization of CD4 CTL suggests their potential significance for therapeutic purposes. However, in order to develop effective CD4 CTL therapy it is necessary to understand the differentiation and generation of these cells. Although the mechanisms regulating development of various CD4+ Th subsets have been clarified in terms of the cytokine and transcription factor requirement, the CD4 CTL differentiation mechanism remains elusive. These cells are thought to be most closely related to Th1 cells secreting IFNγ and regulated by eomesodermin and/or T-bet transcription factors for their differentiation. However, our studies and those of others have identified CD4 CTLs within other CD4+ T cell subsets, including naïve T cells. We have identified class I-restricted T cell-associated molecule as a marker of CD4 CTL and, by using this marker, we detected a subset of naïve T cells that have the potential to differentiate into CD4 CTL. CD4 CTL develops at sites of infections as well as inflammation. In this review, we summarize recent findings about the generation of CD4 CTL and propose a model with several differentiation pathways.